SPL Token Creation Tools on the Solana Network: Modern Token Creator Platforms - Komarudin Komarudin; Diana Magfiroh (Journal of Management Economic and Financial, 2024)
The rapid growth of the Solana blockchain ecosystem has encouraged the development of various tools that simplify the creation of tokens based on the SPL (Solana Program Library) standard. Previously, issuing a token required deep knowledge of smart contracts and command-line tools. Today, Solana Token Creator platforms allow users to generate tokens instantly without coding. This paper reviews the SPL Token concept, the market need for token generator tools, and highlights platforms such as elabz.io as a web-based Solana token generator.